Oligodendroglial modulation of fast axonal transport in a mouse model of hereditary spastic paraplegia - Julia M. Edgar; Marκ McLaughlin; D. A. Yool; Su-Chun Zhang; Jill H. Fowler; Paul Montague; Jennifer A. Barrie; Mailis C. McCulloch; Ian D. Duncan; James Garbern; Klaus Armin Nave; Ian R. Griffiths (2004)
Oligodendrocytes are critical for the development of the plasma membrane and cytoskeleton of the axon. In this paper, we show that fast axonal transport is also dependent on the oligodendrocyte. Using a mouse model of hereditary spastic paraplegia type 2 due to a null mutation of the myelin Plp gene, we find a progressive impairment in fast retrograde and anterograde transport. Increased levels of retrograde motor protein subunits are associated with accumulation of membranous organelles distal to nodal complexes. Using cell transplantation, we show categorically that the axonal phenotype is related to the presence of the overlying Plp null myelin. Our data demonstrate a novel role for oligodendrocytes in the local regulation of axonal function and have implications for the axonal loss associated with secondary progressive multiple sclerosis.